COMPARATIVE ANALYSIS OF NUTRIENT AND PHYTOCHEMICAL PROFILES OF FLOURS PRODUCED FROM THREE MAIZE (ZEA MAYS) VARIETIES - Okoye, O. I.; Asogwa, C.R.; Owoh, N. P.; Chinze, N.N.; Eze, T. R. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study compared nutrient and phytochemical profiles of flours from three maize varieties: yellow (YCF), white (WCF) and popcorn (PCF) maize. Specifically, the study analysed proximate (moisture, crude protein, fat, ash, crude fibre and carbohydrate) and phytochemical composition (carotenoid, alkaloid, flavonoid) of flours from three maize varieties. Samples were processed using different standard methods. Proximate and phytochemical contents of the samples were analysed using standard methods and data were expressed as mean ± standard deviation. Analysis of variance was used to test for differences and Duncan’s New Multiple Range Test was used to separate and compare the means. A probability level (p – value) of < 0.05 was considered statistically significant. Proximate analysis revealed that popcorn flour exhibited the highest protein (17.95%) and carbohydrate (24.64%) content, while white corn had the highest moisture content (57.13%). Yellow corn recorded the highest crude fiber content (3.36%). Phytochemical analysis indicated that yellow corn contained the highest levels of alkaloids (11.00 mg/100g) content. The yellow corn flour (YCF) had the highest flavonoid (1.77 mg/100g). The alkaloid content was highest (11.00 mg) in YCF and lowest (6.50 mg) in PCF. The carotenoid content was highest (3.54 mg) in WCF and lowest (1.05 mg) in YCF The findings showed that these flours contain essential nutrients and phytochemicals. This suggests that consumption of these flours are important in prevention of mental health related diseases.